Advanced engineering thermodynamics - Bejan, Adrian (John Wiley & Sons, Inc., 2006)
Adrian Bejan's Advanced Engineering Thermodynamics established itself as the definitive volume on this challenging subject. Now, his Third Edition builds on the success of its trailblazing predecessors by providing state-of-the-art coverage in a slimmer, more convenient book.